Pre-Clinical Toxicity Study and Safety Assessment of Candidate Live Pertussis Vaccine for Intranasal Administration - L. N. Sinyashina; E. G. Semin; A. Yu. Medkova; R. A. Siundiukova; G. I. Karataev (Эпидемиология и вакцинопрофилактика, 2019)
Against the backdrop of mass parenteral immunization by present pertussis vaccines the incidence rate of pertussis is recorded in many countries, as well as among adolescents and adults, according to the World Health Organisation data. The number of cases of pertussis complicated to detect is increased, meaning atypical forms and inapparent bacteria carrying. In the presence of appearance of Bordetella pertussis strains of «new» genotype the efficacy of current pertussis vaccines is decreased. Existing epidemiologic situation cries out for development of new, more efficient pertussis vaccines and  improvement of immunization methods and schedules. The most promising for this problem solution are live pertussis vaccines, constructed with genetic engineering methods.The goal  of  present  research  is studying  of  toxicity  and  safety  of  innovative  recombinant  live pertussis  vaccine  for  intranasal administration in animals.Obtained results demonstrate the absence of specific toxicity of candidate vaccine and its use safety in intranasal applying.